Efecto de la adición de tierras diatomeas y CaCO3 en la resistencia a la compresión del cemento Portland - Maldonado Silva, María Fernanda (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
The cement industry is responsible for approximately 7% of global carbon dioxide emissions, prompting the search for alternative approaches to mitigate this environmental impact. One viable alternative is the production of hybrid cements, which can be developed using natural pozzolans such as diatomite. Diatomaceous earth is a readily available material found in the municipalities of Charo, Zacapu, and Zitácuaro in the state of Michoacán. Within this context, the present study proposes a sustainable alternative through the formulation of hybrid cements incorporating alkali-activated calcium carbonate (CaCO₃) with sodium hydroxide NaOH (PA), ordinary Portland cement (OPC), and thermally treated diatomaceous earth (TDC). The aim is to reduce the clinker content in Portland cement and enhance the formation of cementitious products such as calcium silicate hydrate (C-S-H), assessing their effect on compressive strength. Various mixtures were designed with different replacement percentages and water-to-cement (w/c) ratios, and their mechanical performance was evaluated at 3, 7, and 28 days under two curing conditions: humid room curing and immersion curing. Experimental results showed the highest compressive strength in the cement–diatomite (CD) paste, reaching 396.93 kg/cm² under immersion curing. Through X-ray diffraction (XRD), scanning electron microscopy (SEM), elemental analysis, and chemical mapping, the formation of hydrated phases such as ettringite and C-S-H was confirmed, along with evidence of surface carbonation. The thermal treatment of diatomaceous earth and the alkali activation of CaCO₃ represent a sustainable and effective alternative for the partial replacement of Portland cement, contributing to the reduction of the environmental footprint of the cement industry.

La industria cementera es responsable de las emisiones de alrededor del 7% de dióxido de carbono en el mundo, por ello se han buscado diferentes alternativas para aminorar este impacto. Una alternativa viable es la producción de cementos híbridos los cuales se pueden obtener a través de puzolanas naturales como la diatomita. Las tierras diatomeas son un material disponible y de fácil acceso en los municipios de Charo, Zacapu y Zitácuaro en el estado de Michoacán. Dentro de este contexto, en este trabajo se propone una alternativa sostenible mediante la formulación de cementos híbridos, utilizando CaCO3 activado alcalinamente con NaOH (PA), cemento Portland ordinario (CPO) y tierras diatomeas sometidas a tratamiento térmico previo (TDC). Se busca reducir el contenido de clinker en el cemento Portland y potenciar la formación de productos cementantes como hidróxido de silicato de calcio (C-S-H), evaluando su efecto en la resistencia a la compresión. Se propusieron diferentes mezclas con variaciones en el porcentaje de reemplazo y la relación agua/cemento (A/C), se evaluó su desempeño mecánico a los 3, 7 y 28 días bajo dos tipos de curado: curado en cuarto húmedo y curado por inmersión. Los resultados experimentales muestran la mejor resistencia a la compresión en la pasta cemento-diatomita (CD), con un valor de 396.93 kg/cm² bajo curado por inmersión. A través de análisis por difracción de rayos X (DRX), microscopía electrónica de barrido (MEB), análisis elemental y mapeos químicos, se confirmó la formación de fases hidratadas como la etringita y las fases C-S-H, además de evidencias de carbonatación superficial. El tratamiento térmico de las tierras diatomeas y la activación alcalina del CaCO₃ representan una alternativa sostenible y eficaz como sustituto parcial del cemento Portland, contribuyendo a la reducción del impacto ambiental de la industria cementera.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Metalurgia y Ciencias de los Materiales
Keywords: info:eu-repo/classification/cti/7; IIMM-M-2025-1019; Cemento híbrido; Tierras diatomeas; Reacción puzolánica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19397